Produktivitas Karyawan Ditinjau dari Disiplin, Lingkungan dan Insentif Kerja pada PT Iskandartex Solo - Fitriani, Alfira Putri; Diyah, Ida Aryati; Maryam, Siti (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the discipline, environment and work iincentives simultaneously or partially on employee productivity at PT. Iskandartex Solo. This study used a quantitative descriptive approach, the population iin this study were employees of PT. Iskandartex with a total of 900 with a simple random sampling technique, namely using quota sampling by directly determining the number of samples to be studied, namely employees iin the production department, totaling 80. Data was collected by distributing questionnaires. F test, t test, multiple llinear regression and coefficient of determination (R2) were used to analyze the data. The results of the study show that discipline, work environment and iincentives have a simultaneous and significant effect on employee productivity. Keywords: Employee Productivity, Discipline, Environment, and Incentives